2015
DOI: 10.1016/j.ijid.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Level of adherence and predictors of adherence to the Option B+ PMTCT programme in Tigray, northern Ethiopia

Abstract: The adherence level was found to be reasonably good. Counselling on medication and HIV status disclosure were positive predictors of adherence to Option B+ PMTCT drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
114
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 18 publications
8
114
4
1
Order By: Relevance
“…Indeed, we also reported an association between non-disclosure and lower uptake of both maternal and infant ARVs for PMTCT (Kinuthia et al, 2015). These findings are consistent with studies reporting suboptimal uptake and adherence to PMTCT regimens in women who had not disclosed their HIV status (Ebuy, Yebyo, & Alemayehu, 2015; Jasseron et al, 2013; Kinuthia et al, 2011; Spangler, Onono, Bukusi, Cohen, & Turan, 2014) and add to the literature on disclosure and MTCT. Strategies to maintain confidentiality and facilitate disclosure to male partners are needed to maximize PMTCT effectiveness (Kinuthia et al, 2011; Schechter et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, we also reported an association between non-disclosure and lower uptake of both maternal and infant ARVs for PMTCT (Kinuthia et al, 2015). These findings are consistent with studies reporting suboptimal uptake and adherence to PMTCT regimens in women who had not disclosed their HIV status (Ebuy, Yebyo, & Alemayehu, 2015; Jasseron et al, 2013; Kinuthia et al, 2011; Spangler, Onono, Bukusi, Cohen, & Turan, 2014) and add to the literature on disclosure and MTCT. Strategies to maintain confidentiality and facilitate disclosure to male partners are needed to maximize PMTCT effectiveness (Kinuthia et al, 2011; Schechter et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed higher adherence rate as compared to study in Tigray accounted 87.1% among pregnant women [11] and other studies in Ethiopia also documented among adult ART patients such as 81.2% and 82.8% in Addis Ababa [14,15] and 81.1% in Afar [18]. This might be due to difference in study participants, adequate adherence counseling and good educational status in the study area.…”
Section: Discussioncontrasting
confidence: 51%
“…One study in Tigray showed that 87.1% HIV positive pregnant women were adherent to Option B+ PMTCT drugs. The main reason for nonadherence was forgetfulness [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Couple HIV testing and disclosure has been shown to increase women's adherence to both antiretroviral therapy (ART) and prevention of mother to child transmission regimens, including Option B+ (lifelong ART for HIV-infected pregnant women). 1517 Increasing HIV testing in males reduces transmission to their female partners, while also averting morbidity and mortality in men associated with late ART initiation. Men are less likely than women to undergo HIV testing, less likely to start ART, and more likely to seek care at advanced disease stages, interrupt treatment, and die on ART.…”
Section: Introductionmentioning
confidence: 99%